2012
DOI: 10.1111/j.1439-0523.2012.01952.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci (QTL) for Fusarium ELISA compared to QTL for Fusarium head blight resistance and deoxynivalenol content in barley

Abstract: Fusarium head blight (FHB) and deoxynivalenol (DON) mycotoxin produced by Fusarium graminearum reduce barley yield and quality worldwide. An enzyme-linked immunosorbent assay (ELISA) using an antibody specific to Fusarium was proposed as an alternative for measuring FHB instead of counting infected kernels per spike. Cleistogamy (closed flowering) may be an avoidance mechanism for FHB resistance. This study was conducted to determine whether quantitative trait loci (QTL) for Fusarium ELISA were colocated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…On the contrary, grain yield per hectare had highly significant and and positive correlation with thousand grain weight and significant positive correlation with spike length and non-significant positive correlation with peduncle length, plant height and biological yield. This is supported by similar findings from Chaudhary, (1977), Solanki and Bakshi (1973), Gonzalez et al (1999), Bhutta et al (1991), Zadeh et al (2010), Chutimanitsakun et al (2011) and Dahleen et al (2012). Although there exists positive relationship between yield and the other components, the negative correlation between some of them cannot make a useful choice for all as a factor in increasing the yield (Danyard and Kannenberg, 1976).…”
Section: Correlation Coefficient Analysissupporting
confidence: 71%
“…On the contrary, grain yield per hectare had highly significant and and positive correlation with thousand grain weight and significant positive correlation with spike length and non-significant positive correlation with peduncle length, plant height and biological yield. This is supported by similar findings from Chaudhary, (1977), Solanki and Bakshi (1973), Gonzalez et al (1999), Bhutta et al (1991), Zadeh et al (2010), Chutimanitsakun et al (2011) and Dahleen et al (2012). Although there exists positive relationship between yield and the other components, the negative correlation between some of them cannot make a useful choice for all as a factor in increasing the yield (Danyard and Kannenberg, 1976).…”
Section: Correlation Coefficient Analysissupporting
confidence: 71%
“…Quantitative trait loci (QTLs) have been identified for quantitative disease resistance in wheat and barley [4]. Furthermore, resistance to both FHB and DON levels have been mapped to all seven barley chromosomes [29,30], and the most common regions related to FHB resistance have been previously reported to be located on chromosomes 2H and 6H [3,25,31]. Other traits, including awned/awnless ears [26] and spike compactness [32], have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…So far, no major resistance gene against FHB has been reported. Numerous biparental mapping studies identified minor‐effect QTL that act additively to confer resistance to FHB (de la Pena et al, 1999; Zhu et al, 1999; Ma et al, 2000; Dahleen et al, 2003; Mesfin et al, 2003; Canci et al, 2004; Hori et al, 2005, 2006; Horsley et al, 2006; Sato et al, 2008; Lamb et al, 2009; Yu et al, 2010; Dahleen et al, 2012). These studies have described QTL for FHB resistance, DON accumulation, and kernel discoloration across all seven barley chromosomes (Kolb et al, 2001; Massman et al, 2011); however, the most important regions for FHB resistance lie on chromosomes 2H, 4H, and 6H.…”
mentioning
confidence: 99%
“…Several of the FHB resistance QTL identified in biparental studies coincide with QTL for low DON concentration (e.g., Dahleen et al, 2003; Mesfin et al, 2003). Moreover, QTL for low FHB severity and reduced DON concentration are often associated with genes or QTL for various agromorphological traits, including the spike‐type locus Vrs1 , heading date, and plant height (de la Pena et al, 1999; Zhu et al, 1999; Ma et al, 2000; Dahleen et al, 2003, 2012; Mesfin et al, 2003; Hori et al, 2005; Horsley et al, 2006; Lamb et al, 2009). The only resistance QTL reported to be independent of these agronomic traits is the one on chromosome 2HL in PI 643302 (Yu et al, 2010).…”
mentioning
confidence: 99%